(untitled) (BSAA arte, 2020)
Cardinal Torquemada (d. 1468) was an important figure in connecting Italian and Northern art. In his exceptional work as ambassador, theologian, and reformer, he received financial support from his uncle Garci Fernández de Torquemada, a wealthy merchant who had business contacts in Flanders, France, and Italy. Rumours spread by the chronicler Hernando del Pulgar concerning a possible ‘judeoconverso’ background for the Cardinal (i.e., a familiar origin in Jewish people converted to Christianity) are unfounded.